Las pirámides de la educación médica: una síntesis sobre su conceptualización y utilidad. - Carlos Domínguez-Torres, Luis; Valentín Vega-Peña, Neil (Revista Colombiana de Obstetricia y Ginecologia)
Objectives: To examine the conceptual underpinnings of learning pyramids, their limitations and some proposed modifications, and to describe their utility. Materials and methods: Starting with a selection of pyramids based on whether graphic design was part of their original design and on their conceptual description, we examined the criticisms they have received and the modifications derived from those observations, and the use given to the pyramids most commonly used in medical education. Results: Five pyramids were included, namely, George Miller, Edgar Dale, Donald Kirkpatrick, Benjamín Bloom and Abraham Maslow. Pyramids describe different aspects of medical education evaluation, either of individuals or of training programs, including competencies, identity, reliability, learning, behavior, results, cognitive complexity and self-realization. Conclusions: As theoretical models, the pyramids examined have contributed to support learning processes in health professions. Their practical utility extends to different specialties and education levels given that they can help faculty optimize curricular design, teaching and evaluation processes. It is important to conduct a local assessment of the effects on health science programs built on these theoretical models.